Coated Copper Wire Calcium Selective Microelectrode for Applications in Dental Medicine - Totu, Eugenia Eftimie; Isildak, Ibrahim; Tavukcuoglu, Ozlem; Agir, Ismail; Yildirim, Ridvan; Nigde, Mustafa; Nechifor, Aurelia Cristina; Cristache, Corina Marilena (REVISTA CHIMIE SRL, 2018)
A coated wire calcium selective microelectrode for biological use was developed, comprising a PVC selective matrix containing calcium ionophore IV coated on copper wire, previously covered with a solid-state contact mixture. The obtained calcium microsensor presented a Nernstian answer in a concentration range of 10(-1) to 10(6) mol/L. The selectivity coefficients over the main interfering ions of biological interest proved that the calcium microelectrode is highly selective. Also, the response time (6s) and repeatability have been determined. The pH variation did not significantly modify the calcium microelectrode answer, being stable over the pH range (6.7-7.3) of interest. The obtained calcium microelectrode is simple, inexpensive and able to give reliable electrochemical response, recommending itself as a solution for assessing the level of inorganic ions of the gingival crevicular fluid and saliva. fluid
Keywords: calcium microsensor; coated wire microsensor; solid-state contact mixture; PVC selective mixture; gingival crevicular fluid; ELECTRODES; Chemistry; Engineering